The molecular basis for development of proinflammatory autoantibodies to progranulin. (July 2015) - Thurner, Lorenz; Fadle, Natalie; Regitz, Evi; Kemele, Maria; Klemm, Philipp; Zaks, Marina; Stöger, Elisabeth; Bette, Birgit; Carbon, Gabi; Zimmer, Vincent; Assmann, Gunter; Murawski, Niels; et al.
Abstract: Recently we identified in a wide spectrum of autoimmune diseases frequently occurring proinflammatory autoantibodies directed against progranulin, a direct inhibitor of TNFR1 & 2 and of DR3. In the present study we investigated the mechanisms for the breakdown of self-tolerance against progranulin. Isoelectric focusing identified a second, differentially electrically charged progranulin isoform exclusively present in progranulin-antibody-positive patients. Alkaline phosphatase treatment revealed this additional progranulin isoform to be hyperphosphorylated. Subsequently Ser81, which is located within the epitope region of progranulin-antibodies, was identified as hyperphosphorylated serine residue by site directed mutagenesis of candidate phosphorylation sites. Hyperphosphorylated progranulin was detected exclusively in progranulin-antibody-positive patients during the courses of their diseases. The occurrence of hyperphosphorylated progranulin preceded seroconversions of progranulin-antibodies, indicating adaptive immune response. Utilizing panels of kinase and phosphatase inhibitors, PKCβ1 was identified as the relevant kinase and PP1 as the relevant phosphatase for phosphorylation and dephosphorylation of Ser81. In contrast to normal progranulin, hyperphosphorylated progranulin interacted exclusively with inactivated (pThr320) PP1, suggesting inactivated PP1 to cause the detectable occurrence of phosphorylated Ser81 PGRN. Investigation of possible functional alterations of PGRN due to Ser81 phosphorylation revealed, that hyperphosphorylation prevents the interaction and thus direct inhibition of TNFR1, TNFR2 and DR3, representing an additional direct proinflammatory effect. Finally phosphorylation of Ser81 PGRN alters the conversion pattern of PGRN. In conclusion, inactivated PP1 induces hyperphosphorylation of progranulin in a wide spectrum of autoimmune diseases. This hyperphosphorylation prevents direct inhibition of TNFR1, TNFR2 and DR3 by PGRN, alters the conversion of PGRN, and is strongly associated with the occurrence of neutralizing, proinflammatory PGRN-antibodies, indicating immunogenicity of this alternative secondary modification. Highlights: The additional, hyperphosphorylated PGRN isoform was only detected in progranulin-antibody-positive patients. The phosphorylation site (Ser81) was located within the epitope region of progranulin antibodies (aa12–112) and the occurrence of hyperphosphorylated progranulin preceded the appearance of progranulin-antibodies. These results strongly suggest the hyperphosphorylation as reason for the breakdown of self-tolerance against PGRN.